Trapped in Desire: A Comparative Study of Identity Diffusion in Anna Karenina and Madame Bovary - Tlonaen, Zuvyati Aryani (NOBEL: Journal of Literature and Language Teaching, 2026)
Two female characters from different cultural backgrounds, Russia and France, in the novels Anna Karenina and Madame Bovary show signs of identity diffusion. This study uses a qualitative method with a content analysis approach. The content analysis procedure includes close reading and understanding the texts, identifying relevant quotes, classifying data, and interpreting the emerging meanings. Data collection is done through documentation by gathering quotes from both novels that reflect identity issues. The research instrument is based on eight indicators of identity diffusion by Kroger and Marcia (2011); lack of exploration, lack of commitment, external influence, lack of self-definition, emotional emptiness, isolation, lack of autonomy from role models, and need for external validation. The data was analyzed using Miles’ et al., (2018) procedure: data reduction, data display, and conclusion drawing. The results show that both Anna and Emma fail to form a stable identity, as indicated by the eight criteria, which eventually leads to their self-destruction. This study offers theoretical and methodological contributions to literature and psychology and helps people understand how unclear identity can lead to personal tragedy, both in fiction and real life. Future studies can explore other identity types in cross-cultural literature and their impact on modern readers.